IMPLEMENTASI HAK KHIYAR DALAM DUNIA BISNIS VIA ONLINE - Hamdani Rokan (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
The era of globalization and free trade that is rife and supported by the advancement of communication technology can expand the space for trade or sale and purchase services on transactions of goods and services. Among the phenomena of absence of khiyar (option rights) it is clear as buying and selling at supermarkets, supermarkets, malls to buying and selling online that all forms of defects, damage and so on that are known to the buyer after buying is no longer the responsibility of the seller and has fully become a consumer risk . The purpose of this study is to provide an in-depth understanding of the legal rules of consumer protection in the business world. So that it is hoped that it can be used as a reference for study material to develop the concept of thinking more logically, systematically and consistently rationally. This study is descriptive analytical so that this paper is expected to be able to provide a general, systematic and comprehensive description of all matters relating to the implementation of the Consumer Protection Law in accordance with the applicable rules. A seller is not allowed to conduct transactions in a false way, then the buyer (consumer) can do the option (cancel) the contract if the item received does not match the criteria indicated by the seller or the item in a defective state.